2010
DOI: 10.1007/s00192-010-1323-x
|View full text |Cite
|
Sign up to set email alerts
|

The prevalence and risk factors of overactive bladder symptoms and its relation to pelvic organ prolapse symptoms in a general female population

Abstract: Introduction and hypothesisTo study the prevalence and risk factors of overactive bladder (OAB) symptoms and its relationship with symptoms of pelvic organ prolapse (POP).MethodsThis is a cross-sectional study including women aged between 45 and 85 years, registered in eight general practices. All women were asked to self complete the validated Dutch translated questionnaires. All symptoms were dichotomized as present or absent based on responses to each symptom and degree of bother.ResultsForty-seven percent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
41
2
7

Year Published

2012
2012
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(55 citation statements)
references
References 30 publications
4
41
2
7
Order By: Relevance
“…A large, cross‐sectional study using multiple linear regression (MLR) and artificial neural networks (ANNs) reported the weak correlation between the symptom of urgency and anatomical findings . These findings confirmed previous reports suggesting that bladder and bowel dysfunction may coexist but not be causally related to prolapse . The mechanism behind the development of urinary and bowel symptoms is multifactorial, including intrinsic and extrinsic factors.…”
Section: Discussionsupporting
confidence: 73%
“…A large, cross‐sectional study using multiple linear regression (MLR) and artificial neural networks (ANNs) reported the weak correlation between the symptom of urgency and anatomical findings . These findings confirmed previous reports suggesting that bladder and bowel dysfunction may coexist but not be causally related to prolapse . The mechanism behind the development of urinary and bowel symptoms is multifactorial, including intrinsic and extrinsic factors.…”
Section: Discussionsupporting
confidence: 73%
“…Fifteen studies made a specific reference to OAB . The others categorised urinary symptoms in a variety of ways including LUTS, UUI, SUI and MUI.…”
Section: Resultsmentioning
confidence: 99%
“…A possible explanation for the late occurrence of OAB symptoms might be formation of fibrosis around the tape or mesh erosion . Obviously, these symptoms could also be the result of physiological changes associated with ageing, since the prevalence of OAB increases with age …”
Section: Methodsmentioning
confidence: 99%